Hung Nguyen-Viet at COP27 side event 'Links between climate change and zoonotic diseases emergence' - Hung Nguyen-Viet (International Livestock Research Institute, 2022)
Hung Nguyen-Viet speaks at the COP27 side event 'Links between climate change and zoonotic diseases emergence—Prevention as a global solution through the example of the PREZODE initiative’.